1996
DOI: 10.1073/pnas.93.20.10595
|View full text |Cite
|
Sign up to set email alerts
|

Negative regulation of hypoxia-inducible genes by the von Hippel-Lindau protein.

Abstract: Inactivation of the von Hippel-Lindau protein (pVHL) has been implicated in the pathogenesis of renal carcinomas and central nervous system hemangioblastomas. These are highly vascular tumors which overproduce angiogenic peptides such as vascular endothelial growth factor/ vascular permeability factor (VEGF/VPF). Renal carcinoma cells lacking wild-type pVYHL were found to produce mRNAs encoding VEGF/VPF, the glucose transporter GLUT1, and the platelet-derived growth factor B chain under both normoxic and hypox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
501
3
19

Year Published

1998
1998
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 797 publications
(534 citation statements)
references
References 35 publications
11
501
3
19
Order By: Relevance
“…We and others have recently shown that GRIM-19 binds to STAT3 and inhibits its gene stimulating functions (Lufei et al, 2003;Zhang et al, 2003). In this regard, GRIM-19 appears to behave like the VHL protein, which binds to transcription factor HIF1 and prevents its gene stimulatory function (Iliopoulos et al, 1996;Maxwell et al, 1999). Among the members of the STAT family, GRIM-19 preferentially associates with STAT3 .…”
Section: Discussionmentioning
confidence: 95%
“…We and others have recently shown that GRIM-19 binds to STAT3 and inhibits its gene stimulating functions (Lufei et al, 2003;Zhang et al, 2003). In this regard, GRIM-19 appears to behave like the VHL protein, which binds to transcription factor HIF1 and prevents its gene stimulatory function (Iliopoulos et al, 1996;Maxwell et al, 1999). Among the members of the STAT family, GRIM-19 preferentially associates with STAT3 .…”
Section: Discussionmentioning
confidence: 95%
“…Although the molecular function of the VHL gene product, pVHL, was initially not known when it was first identified by positional cloning in 1993, 3 observations that oxygen-dependent regulation of hypoxia-inducible genes was lost in VHL-deficient cell lines suggested a role for pVHL in oxygen sensing. [4][5][6] In a seminal paper, Maxwell et al 7 showed that pVHL was critical for targeting the a-subunit of hypoxia-inducible factor (HIF) for oxygen-dependent proteolysis, thus providing a direct molecular link between VHLassociated tumorigenesis and oxygen sensing via HIF. HIFs belong to the PAS (Per-arylhydrocarbon receptor nuclear translocator (ARNT)-Sim) family of basic helix-loop-helix (bHLH) transcription factors and bind DNA as heterodimers.…”
mentioning
confidence: 99%
“…HIF-1 is expressed in response to hypoxia in most cell types and activates the transcription of genes involved in a variety of physiological and cellular processes including vascular endothelial growth factor (VEGF), glucose transport (glucose transporters), glycolysis (glycolytic enzymes), and cell survival (insulin-like growth factor 2) (Semenza, 1999). pVHL defective cells, both in cell culture and in the context of human tumours, constitutively overexpress HIF-1 target genes irrespective of their environmental oxygen concentration (Iliopoulos et al, 1996), due to the constitutive stabilisation of HIF-alpha subunits (Maxwell et al, 1999).…”
mentioning
confidence: 99%